Peran Pemerintah Terhadap Kelompok Tani Di Kelurahan Kamasi Kecamatan Tomohon Tengah - Mandagi, Reinhard Vladimir; Sendow, Martha Mareyke; Waney, Nordy Fritsgerald Lucky (AGRI-SOSIOEKONOMI, 2023)
This research aims to determine the big role of the sub-district government in farmer groups in Kamasi sub-district, Central Tomohon sub-district. This research was carried out in November to January 2023 starting from preparation, data collection to preparing research results reports. The data used in this research are primary data and secondary data. Primary data was obtained directly from the source through surveys and interviews using a list of questions with members of the Farmer's Group, while secondary data was obtained from the Kamasi Village office. Based on the research results, it shows that the government is very good towards farmer groups in collaborating to market agricultural products, assisting with facilities and infrastructure, conducting agricultural training and counseling and facilitating sources of capital for farmer groups to support the farmer group's needs. The Government's role is very good, although it is not optimal in its role in accessing capital sources for farming because there are no Cooperative and Bank financial institutions.